The effects of education on women's participation in decision-making in the family of Barangay of South Fundidor, Molo, Iloilo City - Dalisay, Genifer L.
This family attempts to identify the areas of decision making in the family that are participated in by married women of South Fundidor, Molo City and to find out whether educational attainment of women has any significant effect of women's participation in decision-making in the family., Barangay south Fundidor was chosen as the locale of the study not only for the convenience of the researcher but because of her familiarity of the lcoale that will enable her to gather more data. The respondents of the study are married women aged 20-50 years old, having a nuclear family, either employed or unemployed and are residents of south Fundidor, Molo City. With the use Yamane's formula in determining the sample size, 56 respondents was drawn from the total number of population of 126. With the use of simple frequency and percentage counts , the areas of decision-making in the family that women are more involved in were identified. Women of south Fundidor participate in the economic or financial areas of decision-making and are more involved most particularly in budgeting and buying of home furnishing equipments in budgeting and preparation of food. In the socio-moral areas, they are most particularly involved in the health and sanitation of the family members and in the religious activities of the family. The results of the chi-square test on the other hand revealed that educational attainment affects women's participation in the decision making in the economic or financial areas particularly in budgeting and buying of clothes for the family members and in the budget and preparation of food. In the socio-moral area educational attainment affects women's participation in the decision making in religious activities of the family.